Analisis Filosofis Pendidikan Karakter Menurut Ibnu Maskawaih - Heryana Nugraha; Irawan Irawan; Tedi Priatna (Departement of Mathematics Education, 2024)
The aim of this research is to philosophically analyze character education expressed by Ibnu Maskawaih in the book